The CISG and Common Law Courts: Is There Really a Problem? - Lutz, Henning (Victoria University of Wellington Law Review, 2004)
The United Nations Convention on Contracts for the International Sale of Goods (CISG) is generally perceived as a successful example of unified law with 62 contracting states so far. However, this impressive number has not resulted in an evenly-spread acceptance of the CISG worldwide. The scarcity of CISG-related case law from common law countries has led to the assumption that common law jurisdictions have specific issues with the application of the CISG. This article examines the various explanations for this phenomenon that have been put forward so far, primarily through an analysis of case law. The article disproves the contention that common law jurisdictions, when interpreting the CISG, employ a narrow approach, persistently adhere to common law specific concepts, or are generally reluctant to refer to scholarly writings. It emerges that the CISG is a well-known feature in most common law courtrooms, applied by judges with growing skill and prudence. The article concludes that often common law lawyers are more ignorant and unfamiliar with the CISG than judges and appeals to them to improve their knowledge by taking advantage of the numerous sources of information about the CISG.